Defunding the police in the UK: Critical questions and practical suggestions. Issue 2 (27th February 2022) - Fleetwood, Jennifer; Lea, John
Abstract: Calls to defund the police emerged from Black Lives Matter (BLM) protests of 2020, inspiring USA cities to shift funding from policing to social welfare. Here we consider how defunding might translate to the UK, raising critical questions about our distinct funding arrangements, and social welfare traditions. Next, we consider how the spirit of defunding could be adapted in the UK drawing on the left realist proposition of minimal policing, radically restricting police powers and autonomy. In contrast to many abolitionists, we foresee the state continuing to play an important role in ensuring justice through the development of specialist non‐police led agencies to respond to serious crimes and residual conflicts.